Effect of Air Pre-Oxidation on High Temperature Air Oxidation Behavior of Carbon Steel and Stainless Steel (The International Journal of Engineering & Information Technology (IJEIT), 2024)
In this paper, air pre-oxidation technique wasdeveloped in order to improve the oxidation resistance ofcarbon steel (0.131 wt% C) and stainless steel (304L). Theoxidation behavior of carbon steel and stainless steelspecimens with and without pre-oxidation was studied overthe temperature range 450 to 550°C for up to 120h. Thediscontinuous oxidation behavior of the selectedexperimental materials was tested in static air. The use ofpre-oxidation at 450°C for 5 hours to carbon steel and at500°C for 5 hours to stainless steel showed considerableimprovements to the oxidation kinetics for both carbon steeland stainless steel, especially at relatively low temperatures– 450°C and 500°C. Generally, air oxidation kinetic data ofcarbon steel showed rapid increase of weight compared withstainless steel throughout the selected temperature range.The formation of Cr2O3 layer improved the oxidationresistance of stainless steel. Cr2O3 layer acts as a diffusionbarrier to the reactive species. Also, the oxidation process ofcarbon steel was found to be controlled by the formation ofrelatively thin and adherent layer of Fe2O3, especially at lowexposure temperature (e.g. 450°C). Whereas, at highertemperatures (e.g. 550°C), the pre-formed Fe2O3 layer failedto protect carbon steel from further oxidation even for shortexposure time. The scale formed on carbon steel at 550°Cseverely cracked and spalled off especially, at places ofsample corners. Results of this research revealed that,alloying elements in stainless steel were more beneficial tooxidation resistance than pre-oxidation to steel, throughoutthe whole range of time and temperature of this study.